INTANGIBLE WORK AS A PHENOMENON AND CONCEPT: STATUS IN A WORLD OF INSECURITY AND RESEARCH POSSIBILITIES - Голіков, А. С.; Тягло, В. І. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The article is devoted to the problem of immaterial labor in the modern world as a phenomenon, as well as to the possibilities of studying it using sociological tools - as a category. Immaterial labor is considered by the authors as a specific phenomenon, the formation and spread of which is significantly associated with the world of global capitalism. The article describes the features and aspects of immaterial labor as a phenomenon and as a concept. Based on the developments of P. Bourdieu, M. Lazzarato, G. Standing, the researchers analyze the formation and development of immaterial labor phenomenality and epiphenomenality in the global world. Special attention to the precarious status of immaterial labor and its workers, the ratio of unreliability and precariousness in the nature of immaterial labor is paid. These concepts and ideas are used to study current transformations and attempts to predict future changes in the status, activities and characteristics of immaterial workers in the modern world. The authors argue that social policies and social work in relation to immaterial labor workers cannot be implemented according to modern models and patterns, but must be specified for new conditions. In addition, the authors argue that the unreliability of immaterial labor changes the prospects, limitations and features of both the status of labor itself (in particular, hiding a considerable part of it as labor), and the possibilities of instruments of state regulation, social policy and social work in relation to it: in particular, it turns out that the global world gives rise to whole groups of immaterial labor, included in the precariousness of the economy, the insecurity of social status - and at the same time excluded from social policy and social work. The very phenomenon of (immaterial) labor in this light becomes deinstitutionalized, amorphous, diffuse, constellative, oscillating and opalescent.Key words: insecurity, globalization, social policy, immaterial labor, Maurizio Lazzarato, immaterial labor workers, precariousness.